2016
DOI: 10.1016/j.jphs.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A novel selective prostaglandin E2 synthesis inhibitor relieves pyrexia and arthritis in Guinea pigs inflammatory models

Abstract: Prostaglandin E2 (PGE2), one of the terminal products in the cyclooxygenase pathway, plays an important role in various inflammatory responses. To determine whether selective inhibition of PGE2 may relieve these inflammatory symptoms, we synthesized a selective PGE2 synthesis inhibitor, compound A [1-(6-fluoro-5,7-dimethyl-1,3-benzothiazol-2-yl)-N-[(1S,2R)-2-(hydroxymethyl)cyclohexyl]piperidine-4-carboxamide], then investigated the effects on pyrexia, arthritis and inflammatory pain in guinea pigs. In LPS-stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Other papers reported that mPGES-1 deficiency or a pharmacological inhibition of mPGES-1 also shows the prostanoids' redirection [ 24 27 ]. However, the inhibitory profile against each prostanoid differs among them [ 28 ], suggesting that reactivity may differ depending on the expression profile of terminal synthases in target cells or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Other papers reported that mPGES-1 deficiency or a pharmacological inhibition of mPGES-1 also shows the prostanoids' redirection [ 24 27 ]. However, the inhibitory profile against each prostanoid differs among them [ 28 ], suggesting that reactivity may differ depending on the expression profile of terminal synthases in target cells or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless the extract showed antpyretic activity in dose dependant manner. Prostaglandins have been known since long for their role in the pyrexia (Milton, 1982;Sugita et al, 2016;Engström et al, 2012). So it is obvious that inhibition in prostaglandin pathway could lead to antipyretic potential.…”
Section: Controlmentioning
confidence: 99%